Assessment of voice function and the impact of voice disorders on the quality of life in patients with larynx cancer after surgical treatment - Runcheva, D. A.; Sinaiko, I. O.; Сінайко, Ірина Олександрівна (My University, 2023)
In Ukraine, according to the 2020 cancer registry, the incidence of laryngeal cancer is 5.2 per 100,000 population (the world standard rate is 3.3). The total number of cases of the disease in 2020 is 1845. Among them, 1763 persons are men, 82 - are women.